Experimental research of atomic-absorbtion spectrophotometre with capillary electrothermal atomiser - Loriia, M. H. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The paper contains the results of experimental research of atomic-absorbtion spectrophotometre with Massman atomiser and capillary atomiser. The advantages of spectrophotometre with capillary atomiser are shown in this paper. When this atomiser is used cassual mistakes of measurement, unselective spectral mistakes are decreased and it leads to increaseg of accuracy and sensitivity of the device. Calibration characteristics can be linear and can be calculated theoretically or be marked by one registration point theoretically.